Successful local marine conservation requires appropriate educational methods and adequate enforcement. (February 2015) - Watson, G.J.; Murray, J.M.; Schaefer, M.; Bonner, A.
Abstract: MPAs and stakeholder education are marine conservation cornerstones, but data to assess adherence to regulations and the success of educational methods are missing. Local MPAs have been established to protect inter-tidal mudflats and shore users from bait collection which is a contentious worldwide issue. Video cameras monitored activity and confirmed if collectors adhered to the rules at three UK sites with different MPA systems. An educational approach (a voluntary code leaflet) was also assessed through stakeholder discussion and observation. Fareham Creek and Dell Quay supported a considerable number of collectors with none observed at Pagham Harbour. At Fareham Creek bait dug areas were evident in discrete patches in unprotected and protected areas, but observed collectors mainly used the latter. The failure to exclude collectors is due to the lack of enforcement. At Dell Quay virtually all dug areas were outside protected areas and was confirmed by the camera footage. Success is attributed to regular on-the-ground 'unofficial' enforcement by the managing NGO. Of the retailers, 75% had heard of the code and the majority stated they followed it. However, none of the 26 collectors observed followed a key rule (e.g. backfilling holes). Local marine conservation is relatively cheap and can be effective, but only if: management matches the actual pressure; scientific evaluation for all components (including education) is integrated from the beginning; adequate site enforcement is included; education methods are active, two-way and sustained. Highlights: Using CCTV, bait collection was monitored at MPAs with different management methods. Stakeholder discussion and observation assessed a voluntary code of conduct leaflet. Site 1: majority of collection is in protected areas due to a lack of enforcement. Site 2: collection confined to unprotected areas due to local NGO enforcement. Stakeholders stated they follow the code, but none were observed following a key rule.